Determining subject-specific parameters for a computer simulation model of a one-handed tennis backhand - Glynn, J.; King, M.; Mitchell, S. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
A subject-specific computer simulation model of a one-handed tennis backhand was developed to investigate the mechanisms that may cause injury to the elbow. Subjectspecific parameters for the ball, racket and human were determined. Firing tennis balls from a pneumatic air cannon onto a force plate enabled parameters to be determined for a spring-damper model of a tennis ball. Data from further ball cannon tests allowed the spring constants for the stringbed and the coefficient of friction between the ball and stringbed to be optimised using a computer simulation model. The fundamental modal frequencies of the racket frame were obtained by Doppler laser vibrometry and its inertia parameters were determined from the results of oscillation and balance tests. An elite tennis player performed isovelocity tests at the wrist, elbow and shoulder to establish torque / angle / angular velocity relationships. Inertia parameters of the human segments were calculated from ninety-five anthropometric measurements using a geometric model.